SEISMICITY, FOCAL MECHANISMS, AND STRESS DISTRIBUTION IN THE TRES VíRGENES VOLCANIC AND GEOTHERMAL REGION, BAJA CALIFORNIA SUR, MEXICO - Wong V.; Munguía L. (My University, 2006)
In October 1993 we carried out a seismic monitoring in the Tres Vírgenes volcanic region in order to record the background seismicity associated with the volcanic structures, the geothermal field and the tectonic features of the area. Hypocenters for 257 microearthquakes were located in the volcanic edifices and along the northwest right-lateral, strike-slip La Virgen fault. Focal depths range from close to the Earth surface to about 8 km. Shallow depths occur mainly in the volcanic edifices. Deeper seismic events occurred outside the volcanic area. The duration magnitudes of the located microearthquakes range between 1 and 3. The Vp/Vs ratio and the low-Q values estimated suggest heterogeneous material properties in the volcanic structures mainly toward the El Azufre fault and the El Aguajito Caldera, where hydrothermal activity has been reported. The P- and T-axes of focal mechanisms for 90 microearthquakes suggest that the region is under N-S compression and E-W extension, in agreement with the regional tectonic stress field of the NW-SE right-lateral strike-slip transform fault system of the Gulf of California.
Keywords: BAJA CALIFORNIA SUR; FOCAL MECHANISMS; GEOTHERMAL FIELD; SEISMICITY; TECTONIC STRESS; VOLCANIC STRUCTURES